Physiological responses and toxin production of Microcystis aeruginosa in short-term exposure to solar UV radiation. Issue 1 (30th November 2017) - Hernando, Marcelo; Minaglia, Melina Celeste Crettaz; Malanga, Gabriela; Houghton, Christian; Andrinolo, Darío; Sedan, Daniela; Rosso, Lorena; Giannuzzi, Leda
Abstract : We found a UVBR threshold and different responses were activated depending on the exposure to UVAR or UVBR and their doses. =: no changes; −: decrease; +: increase. The number of signals represents the intensity of the effect. Abstract : The aim of this study was to evaluate the effects of short-term (hours) exposure to solar UV radiation (UVR, 280–400 nm) on the physiology of Microcystis aeruginosa . Three solar radiation treatments were implemented: (i) PAR (PAR, 400–700 nm), (ii) TUVA (PAR + UVAR, 315–700 nm) and (iii) TUVR (PAR + UVAR + UVBR, 280–700 nm). Differential responses of antioxidant enzymes and the reactive oxygen species (ROS) production to UVR were observed. Antioxidant enzymes were more active at high UVR doses. However, different responses were observed depending on the exposure to UVAR or UVBR and the dose level. No effects were observed on the biomass, ROS production or increased activity of superoxide dismutase (SOD) and catalase (CAT) compared to the control when UVR + PAR doses were lower than 9875 kJ m −2 . For intermediate doses, UVR + PAR doses between 9875 and 10 275 kJ m −2, oxidative stress increased while resistance was imparted through SOD and CAT in the cells exposed to UVAR. Despite the increased antioxidant activity, biomass decrease and photosynthesis inhibition were observed, but no effects were observed with added exposure to UVBR. At the highest doses (UVR + PAR higher than 10 275 kJ m −2 ), the solar UVR caused decreased photosynthesis and biomass with only activation of CAT by UVBR and SOD and CAT by UVAR. In addition, for such doses, a significant decrease of microcystins (MCs, measured as MC-LR equivalents) was observed as a consequence of UVAR. This study facilitates our understanding of the SOD and CAT protection according to UVAR and UVBR doses and cellular damage and reinforces the importance of UVR as an environmental stressor. In addition, our results support the hypothesized antioxidant function of MCs.